2021
DOI: 10.1186/s12885-021-08216-6
|View full text |Cite
|
Sign up to set email alerts
|

Is PSA density of the peripheral zone as a useful predictor for prostate cancer in patients with gray zone PSA levels?

Abstract: Background Serum prostate-specific antigen (PSA) is widely used in screening tests for prostate cancer. As the low specificity of PSA results in unnecessary and invasive prostate biopsies, we evaluated the clinical significance of various PSAs and PSA density (PSAD) related to peripheral zones in patients with gray zone PSA level (4–10 ng/mL). Methods A total of 1300 patients underwent transrectal ultrasonography-guided prostate biopsy from 2014 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Many studies have shown that PSAD is more effective than PSA in predicting PCa (15,34,35). Although they only mentioned the gray zone (PSA level upper normal limit 10 ng/mL), our results suggest that a PSA level up to 20 ng/mL could also help predict cancer based on PSAD.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Many studies have shown that PSAD is more effective than PSA in predicting PCa (15,34,35). Although they only mentioned the gray zone (PSA level upper normal limit 10 ng/mL), our results suggest that a PSA level up to 20 ng/mL could also help predict cancer based on PSAD.…”
Section: Discussionmentioning
confidence: 52%
“…Many studies related to PSAD in men with PSA levels in the gray zone (11,15,16) as well as in PSA <20 ng/mL (9,10,13,17,18) have been conducted, we investigate PSAD as a risk factor for PCa in patients with low-to-intermediate risk (PSA levels 2.5-20.0 ng/mL), and found that the risk of PCa increased in this patient cohort when PSAD was 0.218 or higher. In patients with high PSA levels, PCa should be excluded based on TRUS-Bx findings.…”
Section: Discussionmentioning
confidence: 94%
“… 18 and Lee et al . 19 indicated that PZPSAD was better than PSA for the detection of PCa. In this study, we found that PZ-ratio had an advantage over PSA in the diagnosis of PCa, while PSADPZ had no advantage over PSA.…”
Section: Discussionmentioning
confidence: 99%
“…Despite high sensitivity rates of PSA levels in the diagnosis of PC, the low specificity rates yield to unnecessary biopsy procedures. 6 - 8 The PSA cutoff value of 4 ng/ml is considered as a common threshold for the biopsy decision. 2 In the current study, the cutoff value of 4 ng/mL demonstrated high sensitivity and low specificity in the diagnosis of CSPC.…”
Section: Discussionmentioning
confidence: 99%
“…4 , 5 Recent studies underlined that PSAD was a more accurate predictor of PC, having similar or better sensitivity but greater specificity compared to PSA levels. 6 - 8 …”
Section: Introductionmentioning
confidence: 99%